The development and implementation of a new import duty on palm oil to reduce non-communicable disease in Fiji - Jeremaia Coriakula; Marj Moodie; Gade Waqa; Catherine Latu; Wendy Snowdon; Colin Bell (BMC, 2018)
Abstract Background Non communicable diseases (NCD) place a significant health burden on Pacific Island countries including Fiji. Policy interventions to curb NCDs have been implemented in Fiji including a 32% increase in the import duty on palm oil. This study aims to analyse the development and implementation of the increase in palm oil import duty in Fiji. Also, to document the policy process, identify barriers and facilitators during implementation and to examine the impact of the new import duty on import volumes. Methods Data were collected through key informant interviews with private stakeholders, government officials and supermarket managers. Transcripts were analysed thematically. Import volumes were analysed for the 2010-2015 period. Results Facilitators of policy development and implementation included stakeholder awareness of the health implications of palm oil, preparation of a comprehensive policy briefing paper, and inter-sectoral support and leadership. This decrease in the availability of palm oil was encouraging however, it may have been counteracted to some extent by industry relabelling the product as vegetable oil. Conclusions Barriers to policy changes need to be anticipated during the policy development process. Whilst the decline in imports probably reduced population consumption, further research is needed to determine if this translated to a population wide reduction in saturated fat.